2000
DOI: 10.2527/2000.783552x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adipocyte and heart fatty acid-binding protein genes on intramuscular fat and backfat content in Meishan crossbred pigs.

Abstract: Effects of genetic variation in porcine adipocyte and heart fatty acid-binding protein genes, A-FABP and H-FABP, respectively, on intramuscular fat (IMF) content and backfat thickness (BFT) were examined in F2 crossbreds of Meishan and Western pigs. The involvement of each FABP gene in IMF accretion was studied to confirm previous results for Duroc pigs. The F2 crossbred pigs were genotyped for various markers including microsatellite sequences situated within both FABP genes. Linkage analysis assigned the A-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
2
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 25 publications
(36 reference statements)
9
76
2
7
Order By: Relevance
“…The H-FABP gene is, according to our results, associated with IMF and MA, but not with BF. This result is not concordant with the first reports which described a main effect of this gene on BF [8], although more recent works have described this association with only IMF [9,13,14]. Moreover the effect of the gene on IMF in our population was independent of BF content, since the introduction of BF as the covariate in the model did not modify the results, contrarily to those reported by Gerbens et al [8].…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The H-FABP gene is, according to our results, associated with IMF and MA, but not with BF. This result is not concordant with the first reports which described a main effect of this gene on BF [8], although more recent works have described this association with only IMF [9,13,14]. Moreover the effect of the gene on IMF in our population was independent of BF content, since the introduction of BF as the covariate in the model did not modify the results, contrarily to those reported by Gerbens et al [8].…”
Section: Discussioncontrasting
confidence: 94%
“…Candidate gene analyses are usually performed in experimental crosses by the application of models where the QTL effects are not fitted [9]. When these kinds of models are used, the linkage disequilibrium between the real QTL and the candidate gene could lead to a wrong association for the candidate gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gerbens et al [17] localised the adipocyte fatty acid-binding protein (A-FABP) gene on SSC 4 and suggested it might control fat distribution in pigs. Yet, further studies [18] did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 78%
“…Johansson et al [36] reported relatively small differences in fatty acid composition for pigs with and without the RN -allele. In pigs, polymorphisms in the H-FABP gene have been associated with variability in intramuscular fat content, largely independent of backfat thickness [25,26], but to our knowledge no reports on the possible changes in fatty acid composition are available yet. Interestingly, in a QTL mapping study using an F 2 cross between Iberian × Landrace pigs, Pérez-Enciso et al [61] concluded that the metabolism and(or) deposition rate of linoleic acid is under (partial) control of a QTL on chromosome 4, and that the effect of the QTL was not an artifact caused by the differences in backfat thickness.…”
Section: Porkmentioning
confidence: 99%